2015 IEEE Symposium on Security and Privacy 2015
DOI: 10.1109/sp.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

What the App is That? Deception and Countermeasures in the Android User Interface

Abstract: Abstract-Mobile applications are part of the everyday lives of billions of people, who often trust them with sensitive information. These users identify the currently focused app solely by its visual appearance, since the GUIs of the most popular mobile OSes do not show any trusted indication of the app origin.In this paper, we analyze in detail the many ways in which Android users can be confused into misidentifying an app, thus, for instance, being deceived into giving sensitive information to a malicious ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 20 publications
1
77
0
Order By: Relevance
“…However, at present, there are quite a few prior systems which can detect such attacks (Bianchi et al 2015;Akhawe et al 2014;Huang et al 2015a). …”
Section: Limitationmentioning
confidence: 99%
“…However, at present, there are quite a few prior systems which can detect such attacks (Bianchi et al 2015;Akhawe et al 2014;Huang et al 2015a). …”
Section: Limitationmentioning
confidence: 99%
“…Another defense against the GUI statemanipulation attacks proposed by Bianchi et al tries to provide explicit and secure indicators to keep the user informed about which app runs in the foreground at all times. 20 Such defense is tailored to attacks similar to Activity inference. In contrast, we believe application restart can be used as a general cyber maneuver against many types of side-channel attacks.…”
Section: Security: Moving Target Defensementioning
confidence: 99%
“…Recently, Bianchi et al [2015] have developed a tool for the android operating system designed to prevent malicious apps executing cosmetic (DV1), behavioural (DV2) or both cosmetic and behavioural deception (DV3). This can include spoofing an applications appearance or generating misleading visual cues on top of legitimate applications by capturing and analysing application programme interface (API) calls to the android graphical user interface.…”
Section: Technicalmentioning
confidence: 99%
“…They are highly appropriate for the software-based locally distributed (MD1-L), oneoff (ES1) attacks, which are generally difficult to defend against, but have seen a relative underinvestment in application against deception techniques (DV1-3). However, as recent research has shown [Bianchi et al 2015], sandboxing can be effective in identifying semantic attacks that implement both behavioural and cosmetic deception. Therefore, sandboxing mechanisms are likely to offer a viable focus of future research against deception techniques.…”
Section: Attack Vs Defence Matrixmentioning
confidence: 99%